Role of bronchoalveolar lavage, transbronchial needle aspiration with bronchial biopsy correlation in lung tumours and immunohistochemistry wherever required - Sheikh, Nazia T.; Nabi, Zarkah; Mir, Faizaan; Shah, Parveen; Rasool, Zubaida; Jan, Rafi A. (International Journal of Research in Medical Sciences, 2019)
Background: Lung cancer is most frequently diagnosed major cancer in the world and the most common cause of cancer mortality worldwide. It comprises about 17% of the total new cancer cases in males and 23% of the total cancer deaths. The objectives of this study were to compare bronchial biopsy, BAL and TBNA in diagnosing lung malignancies and IHC wherever required. Methods: The study was conducted at Sher-i-Kashmir Institute of Medical Sciences Srinagar, India in the department of Pathology. It was a prospective study over a period of 1½ years from June 2015 to December 2016. All patients clinically/ radiologically suspected of lung malignancies who presented between June 2015 to December 2016 and underwent bronchial biopsy, BAL (washings) and TBNA were included in the study. The study included only those cases where BAL, TBNA and bronchial biopsy were done simultaneously. Results: Out of a total 117 clinically suspected cases of lung cancer, tumor was found in 103 cases (103/117) by biopsy, 51 cases by BAL (51/117) and 64 cases by TBNA (64/117). The total number of false positive cases and false negative cases by BAL were 6 and 58. Sensitivity of BAL was found to be 43.69% and specificity 57.14%. The total number of false positive cases and false negative cases by TBNA were 7 and 46. Sensitivity and specificity of TBNA was found to be 55.34% and 50.0%. Conclusions: Thus, in the present study yield of diagnosis was highest with the bronchoscopic biopsies and in maximum number of cases with a sensitivity of 88.034%, and specific histologic diagnosis was made by biopsies and IHC only. Though BAL and TBNA were inferior to bronchial biopsy in diagnosing lung malignancies but these were effective for peripheral lung malignancies and when the patient was at risk of haemorrhage.